Сучасні рішення управління розподілом аероіонних полів - Строкань, Оксана Вікторівна; Строкань, Оксана Викторовна; Strokan, Oksana; Литвин, Юлія Олександрівна; Литвин, Юлия Александровна; Lytvyn, Yulia (Вид-во МДПУ ім. Богдана Хмельницького, 2017)
UK: Робота присвячена опису алгоритму аероіонного розповсюдження від штучних джерел аероіонізації у приміщеннях з комбінованою розрахунковою площиною та можливість його реалізації на мобільних пристроях. Запропонований алгоритм дозволяє моделювання розподіл аероіонного поля у графічному вигляді для зазначених приміщень, визначати зони аероіонного комфорту і дискомфорту і на основі цього виконувати управляючі впливи на картину аероіонного розподілення у заданому середовищі. Управління аероіонним розподіленням ґрунтується на використанні геометричної моделі розподілення від’ємних аероіонів і здійснюється шляхом оптимального розміщення джерел аероіонного випромінювання в заданій робочій зоні. Дана система реалізована на мобільних засобах з операційною системою Android. EN: The paper considers the simulation of distribution of dispersed aerial ions in space from artificial sources of aerial ionization using the Android Studio software environment. The algorithm for determining and providing optimal aerial ion distribution from artificial aerial ionization sources in space from one or more aerial ionizers is proposed. Ensuring of optimal aerial ion distribution is based on the geometric model of distribution of dispersed aerial ions and is supported by optimal placement of aerial ion radiation sources in a given working area. The peculiarity of the proposed algorithm is the calculation of aerial ion distribution for the combined breathing zone, when a horizontal zone of breathing becomes an inclined one. The proposed algorithm is the basis for software of the automated system for calculating the optimal aerial ion mode of the working environment. The proposed software system is a closed system and performs information, control and auxiliary functions. The software system comprises two modules: a module of input parameters and a modeling module, which allows to simulate the aerial ion distribution in space from artificial sources of aerial ionization. The module of input parameters serves to initialize the input parameters, such as the length and width of the calculated zone, the type, capacity and number of ionizers. The simulator module calculates the aerial ion distribution of one and more sources of aerial ion distribution in a given plane at two modes: at given (fixed) coordinates of the source and in an interactive mode when a user is able to freely adjust (move the screen) the location of the sources. The output block of the results serves to output the calculation results: graphically and numerically, on the screen of the device. The data transfer unit allows to get simulation results of isolines on a plane to be generated as a report and corrected by mail online. The purpose of this work is to develop an algorithm for determining aerial ion distribution on a combined calculated plane for software on the Android Studio basis. The paper presents the algorithm for determining the aerial on distribution in the working zones with a combined breathing zone, which is implemented using the Java programming language in the Android Studio (AS) development environment. The software module is developed in Android Studio for the Android (version 4.2 - 5.0) operating system The developed system is mobile and allows a user to use it at any time from any mobile device with the installed Android version. This advantage of the mobile system is a scientific novelty in this problem area. The system guarantees the automation of the process of aerial ion devices placement effectively, resulting in placement of working places in the most favorable locations for work.
Modern solutions of aerial ion field distributions
Keywords: модуль; мова програмування; аероіонне розподілення; Android Studio; нахилена площина; алгоритм; module; programming language; air and ion distribution; Android Studio; inclined area